Unravelling the evolutionary history and promoting conservation genetics of Anadenanthera colubrina var. cebil (Leguminosae), a paradigmatic species in Seasonally Dry Tropical Forests - Zerda Moreira, Andrea (2024)
Seasonally Dry Tropical Forests exhibit a patchy distribution throughout the Neotropics and are considered to be the most threatened tropical forests in the world. Nonetheless, their conservation has often been neglected in comparison to efforts directed toward other biomes. The distribution pattern of Anadenanthera colubrina (Vell.) Brenan var. cebil (Griseb) Altschul allows an adequate mapping of this biome the SDTFs. The main objectives of this work are to study the historical processes that determined the current distribution of the SDTFs under the hypothesis that the demographic history of the remaining fragments of SDTFs in Argentina leads back to a single event of ancestral divergence, and identify Argentinean localities with priority for conservation. Plastid genetic diversity of A. colubrina var. cebil from northern Argentina is characterized using three plastid microsatellite loci. From this genetic characterization, population genetics, and Bayesian inference were carried out. The results from Approximate Bayesian Computations show that the Misiones and Piedmont Subandean nuclei diverged from an ancestral population in the early Neogene while the Formosa population derived from the Misiones nucleus in the late Neogene. Two out of five locations from the Misiones nucleus and three of nine locations from the Subandean Piedmont nucleus are proposed as priority conservation areas.